PRODUCTION OF BIOFERTILIZER USING GOAT DUNG, CHICKEN DUNG, PINEAPPLE PEELS AND CITRUS PEELS (FUDMA JOURNAL OF SCIENCES, 2023)
This study aimed at evaluating the efficacy of composed Biofertilizers from Pineapple and Orange (Citrus) Peels blended with Goat dung and Chicken dung.Organic wastes comprising goatdung, chiken dung, Pineapple waste and Citrus wastes were collected from the Dutsin-Ma vegetable Wednesday market, The agro waste was mixed and put into a digester to which 500 mL of water and 200 g of rumen content were also added. The digester was then tightly closed and a rubber pipe were put on top of the digester so as to allow the gas to escape. Sorghum seeds (10) were then planted using two polythene bags. The organic biofertilizer was applied to one polythene bag at 500 g and the other without treatment (control). The plant length and number of leaves were determined. Results obtained revealed that, the composed Biofertilizer significantly(p
Keywords: Biofertilizer; Cow dung; Pineapple peels; Citrus peels